From the Maccabees to the Mishnah - Cohen, Shaye J. D. (Westminster John Knox Press, 2014)
"This is the third edition of Shaye J.D. Cohen's important and seminal work on the history and development of Judaism between 164 BCE to 300 CE. Cohen's synthesis of religion, literature, and history offers deep insight into the nature of Judaism at this key period, including the relationship between Jews and Gentiles, the function of Jewish religion in the larger community, and the development of normative Judaism and other Jewish sects. Cohen offers students more than just history, but an understanding of the social and cultural context of Judaism as it developed into the formative period of rabbinic Judaism. This new edition includes a brand-new chapter on the parting of ways between Jews and Christians in the second century CE. From the Maccabees to the Mishnah remains the clearest introduction to the era that shaped Judaism and provided the context for early Christianity."--Amazon.com